If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2 + -1x) = 2(6x + -3) (2 * 3 + -1x * 3) = 2(6x + -3) (6 + -3x) = 2(6x + -3) Reorder the terms: 6 + -3x = 2(-3 + 6x) 6 + -3x = (-3 * 2 + 6x * 2) 6 + -3x = (-6 + 12x) Solving 6 + -3x = -6 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 6 + -3x + -12x = -6 + 12x + -12x Combine like terms: -3x + -12x = -15x 6 + -15x = -6 + 12x + -12x Combine like terms: 12x + -12x = 0 6 + -15x = -6 + 0 6 + -15x = -6 Add '-6' to each side of the equation. 6 + -6 + -15x = -6 + -6 Combine like terms: 6 + -6 = 0 0 + -15x = -6 + -6 -15x = -6 + -6 Combine like terms: -6 + -6 = -12 -15x = -12 Divide each side by '-15'. x = 0.8 Simplifying x = 0.8
| 3(2x-7)=4(3+x) | | 14x^4+14x^3-x^2-x=0 | | -4x-19=-99 | | 6x-21=12+4x | | 5z-2z=3z-9+8z | | (((1.5b*b))/(1.5b*b))=50 | | 4z/(-16)=-6 | | -1-5s+6s=5 | | (1.5b*b)=50 | | 4p*2q=30 | | 55r^2-14r-23=0 | | 11+4x=7(x-1) | | 5z-9z=-7z-7-z | | 40=x(x+3) | | 2x+x/2+x+20=580 | | (5w+1)(2-w)=0 | | (1.5*b)*b=0 | | 1.5b*b=0 | | X*2=-9x-8 | | 3x-5-2x=5-12 | | 0.5(4x-2)= | | (5x-90)=2x+30 | | C-6c=0 | | (11r+6)(5r-4)=0 | | Y=0.6(100)+b | | 6n^2/2 | | x+13=5x | | 5(x)=5(2x-3) | | R=b^2+1 | | (5x)2=15x-45 | | 3c-1=c | | 3x-5-x=2x-3 |